Urban arborization in public pathways of four cities in east Mato Grosso do Sul, Brazil - Frederico Augusto Guimarães Guilherme; Michelly Cristina Silva; Daniella Nogueira Moraes Carneiro; Hellen Cristina Alves Nascimento; Kaila Assis Ressel; Wendy Carniello Ferreira (Ornamental Horticulture, 2018)
The study of urban arborization can generate great contributions to urban planning, mainly for new and fast-growing cities. Aiming quantifying and qualifying urban arborization in Cassilândia, Chapadão do Sul, Costa Rica and Paranaíba, in Mato Grosso do Sul State, Brazil, we performed a survey of tree species present in 30 blocks of each city. All trees were evaluated regarding tree size, planting site, pruning and physical conservation status. The species were classified native or exotic. There were 3180 individuals and 89 species, with the highest abundance of Brazilian native trees (69%), although the richness of exotic species was higher (78%). Chapadão do Sul had the largest individuals number and Paranaíba, the smallest. The diversity index was low for all cities, especially because of the large number of oitizeiros (Licania tomentosa) registered, totaling more than half of the trees surveyed. The widespread use of only one species, as found for the oitizeiro in this study, is not recommended because it reduces diversity and increases the chances of diseases and pests in trees in the urban environment. However, it was observed a high incidence of species used in urban arborization, and tree maintenance aspects, such as pruning, were satisfactory in the four studied cities.